Incorporating information about risk stratification into a bowel cancer screening information leaflet: a think aloud study and user testing process - Taylor, Lily C.; Dennison, Rebecca A.; Usher-Smith, Juliet A. (Frontiers in Cancer Control and Society, 2025)
BackgroundCommunication of concepts relating to risk and risk assessment can be challenging for lay individuals to understand. As we move toward risk-stratified screening for bowel cancer, it is necessary to identify public information needs and explore understanding of communication about risk stratification and personal cancer risk as this may have implications for screening uptake. We aimed to develop and test comprehension of a screening leaflet relating to risk-stratified fecal immunochemical test (FIT) screening intervals and to explore participant attitudes toward stratified intervals for bowel cancer screening.MethodsWe adapted an existing NHS England bowel cancer screening leaflet to communicate a bowel cancer screening programme with risk-stratified screening intervals. The leaflet was used in 13 think aloud interviews to elicit areas of misunderstanding and potential alteration. We analyzed the interviews using codebook thematic analysis and made changes based on our findings. We then tested comprehension of the final leaflet with a further 20 participants in a user testing survey. We also analyzed attitudes toward risk-based bowel screening thematically.ResultsThe think aloud interviews identified 42 areas of the adapted leaflet that required improvement and 35 of these were incorporated into the final version. Changes included clarifying terminology, improving layout including greater use of bullet points, and resolving areas of misunderstanding. They also suggested additional information to mitigate cancer worry. At least 90% of user testing participants answered each true or false statement correctly after reading the final version of the leaflet.ConclusionsSpecific elements of the initial risk-stratified leaflet required improvement; after revision, user testing indicated that a minimum threshold of comprehension had been achieved in the final version. Based on the information provided in this leaflet, a risk-stratified approach to bowel cancer screening was considered acceptable overall. With appropriate care taken to develop materials, the public are, therefore, able to understand information about risk-based bowel screening programmes delivered as part of population-based communications.